1999
DOI: 10.1007/s002689900613
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Seeding following Laparoscopy: International Survey

Abstract: The aim of the study was to determine if tumor seeding during laparoscopic surgery for cancer is a rare event or a typical complication of this procedure. Laparoscopic staging and treatment of intraabdominal tumors is increasing in gastroenterology, gynecology, and general surgery. A total of 1052 questionnaires were mailed to surgical department chairmen, members of the German Society of Surgery, Swiss Association for Laparoscopic and Thoracoscopic Surgery, and Austrian Society of Minimal Invasive Surgery ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
1
10

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(182 citation statements)
references
References 54 publications
7
164
1
10
Order By: Relevance
“…However, LC may increase the risk of port site recurrence and peritoneal dissemination as a result of bile leak associated with gallbladder injury [159][160][161]. In patients with incidental gallbladder carcinoma, which is found after cholecystectomy, the ratio of port site recurrence or peritoneal dissemination is reported relatively high with 10-18% and the period until recurrence is relatively short with 6-10 months [162][163][164][165][166][167][168][169][170].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…However, LC may increase the risk of port site recurrence and peritoneal dissemination as a result of bile leak associated with gallbladder injury [159][160][161]. In patients with incidental gallbladder carcinoma, which is found after cholecystectomy, the ratio of port site recurrence or peritoneal dissemination is reported relatively high with 10-18% and the period until recurrence is relatively short with 6-10 months [162][163][164][165][166][167][168][169][170].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…Recent data indicate that laparoscopy cancer resection does not increase the risk of local recurrence or wound metastasis compared to that associated with open surgery [4,11,17]. However, Paolucci et al [18] observed high rates of abdominal wall metastases (port site metastases) after the laparoscopic resection of occult gallbladder carcinoma. These data on occult cancer are of particular relevance to the role of laparoscopic surgery for appendix neoplasms, which are nearly always resected as occult tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake of contrast and the use of Valsava maneuver are recommended to increase the diagnostic accuracy [2]. Furthermore, in such a case with intraabdominal malignancy, tumor seeding along the trocar tract should be always kept in the differential diagnosis [8], which can be well delineated by both imaging tools. Another potential causes comprised a post-surgical seroma or hematoma, which corresponded the characteristics of the present tumor with the size varying according to different postures.…”
Section: Discussionmentioning
confidence: 99%